Perubahan Sel Imun Pulpitis Akibat Biomodulasi Laser GaA1As - Nugrohowati Nugrohowati (Faculty of Dentistry, Universitas Indonesia, 2015)
The objective of this study was to disclose the effect of GaA1As laser biomodulation on pulpitis immune response. The use of laser is still disputable, because of the biomodulation effect of laser remains unclear, particularly on immune response of pulpitis. Laser is  astressor because it produces stress wave that may cause stress on pulp. Modulation of immune system occurred in each variable of immune system component was considred to be GAS (General Adaptation Syndrome). The applied design of this research was experimental clinical trial that involved laser application on those reversible pulpitis and irreversible pulpitis. Each group consist of 10 samples. To identify biomodulation effect of 2 minutes, 5 minutes laser exposure in reversible and irreversible pulpitis, manova test was done. The different result of biomodulation effect on the control group was only indicated by the exposure of GaAIAs laser for 5 minute in reversible pulpitis on decreasing macrophage, T helper, T cytotoxic, IgM and increasing IgG.